Effect of steam explosion on phenolics and antioxidant activity in plants: A review. (June 2022) - Wan, Fachun; Feng, Chengfeng; Luo, Kaiyun; Cui, Wenyu; Xia, Zhihui; Cheng, Anwei
Abstract: Background: Steam explosion (SE) with its dual effect of high temperature and high pressure has gradually been applied in food pretreatment. The process of SE treatment involves various mechanisms: acid-based hydrolysis, thermal degradation, mechanical-like disruption, hydrogen bond destruction and structure rearrangement. Phenolic compounds, as natural secondary metabolites, are found in different forms depending on their association with the food matrix, and exert significant antioxidant activity to improve health benefits. Scope and approach: In this review, we provide a thorough summary regarding on the working principle of SE, the forms of phenolics present in plant, the effects of SE on the concentration and compounds of phenolics, their antioxidant activity including cellular antioxidant activity, the microstructure of the plant matrix, and the application of SE. Key findings and conclusions: Phenolic acids and flavonoids are common phenolic compounds. The different forms of phenolics present in the plant matrix, include free and bound phenolics, or free, esterified, glycosidic and insoluble-bound forms. During SE processing, explosion temperature/pressure and residence time were the main factors that influenced the extraction and conversion of plant phenolics. In general, the effect of SE on phenolic extraction showed a trend of increasing first and decreasing later, and finally, it reached a balanced state with the dissolution and degradation of phenolic compounds. The optimal SE conditions depend on the pretreatment strategy and physical accessibility of the raw material. Under optimal conditions, SE can increase the release of phenolics and enhance their antioxidant activity. There was a positive correlation between phenolics and antioxidant activity. SE can break down the glycosidic linkages, and ester and β-O-4 ether bonds, which leads to an increase in carboxyl and phenolic hydroxyl groups. The SE process can enhance the cellular antioxidant activity of free phenolics, but has the opposite effect on bound phenolics. Regarding the microstructure, the SE can increase the porosity and pore volume of the material, which is beneficial to solute-solvent accessibility and internal mass transfer in the phenolic extraction process. However, the migration and transformation mechanism of SE on phenolics is still not clear. More studies need to focus on the conversion mechanism of SE on bioactive components and further expand the application scope of SE. Highlights: Steam explosion (SE) is gradually being applied to food pretreatment. SE improves solute-solvent accessibility by altering the porosity of biomass. The effect of SE on phenolic yield generally shows a trend of first increasing and then decreasing. SE increases phenolic hydroxyl groups by breaking glycosidic, ester and β-O-4 ether bonds. Optimal SE conditions increase the phenolic yield and antioxidant activity.